Understanding the health context to inform global health efforts - Dr. David A Tarantino, Jr., MD (Elsevier, 2014)
Background: Effective design and implementation of global health programmes requires a comprehensive and holistic understanding of the health circumstances of a given locality. At present, no widely accepted framework or construct for education and training in this specialty exists. Methods: As part of a US Government research grant, the Center for Disaster and Humanitarian Assistance Medicine (CDHAM) at the Uniformed Services University did an analysis of existing and potential constructs for comprehensive understanding of health circumstances. Methods included a comprehensive literature review, a gap analysis, subject matter expert interviews, construct development exercise, and ongoing validation. Findings: CDHAM has developed a prototype framework for assessment and analysis of the health context of a given locality, including five essential domains: geopolitical/economic considerations; sociocultural considerations; health-specific cultural considerations; determinants of health; and health systems analysis. This framework is being taught in its general form at the Uniformed Services University and to personnel engaging in global health efforts. The health construct framework has also been applied specifically and in detail to Iraq and Afghanistan, yielding valuable insights regarding the health context, which are being used in training for personnel engaging in health efforts in these countries. Interpretation: The Health Context Construct for comprehensive and holistic understanding of the health circumstances of a given locality, developed by CDHAM, is showing promise as an instrument to inform and optimise the design and implementation of global health efforts. The Health Context Construct should be further validated and incorporated into global health curricula where appropriate. Funding: Defense Language National Security Education Office (DLNSEO).